2010
DOI: 10.1253/circj.cj-10-0105
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Contractile Activity During Postconditioning Enhances Cardioprotection by Restoring Sarcolemmal Dystrophin Through Phosphatidylinositol 3-Kinase

Abstract: Background: Although ischemic postconditioning (IPost) confers cardioprotection by protecting the mitochondria though the activation of phosphatidylinositol 3-kinase (PI3K), a potential drawback of IPost is impairment of aerobic ATP generation during reperfusion by repeated ischemia. This decrease in ATP might inhibit the restoration of sarcolemmal dystrophin, which is translocated during ischemia, and render cardiomyocytes susceptible to contraction-induced oncosis. Methods and Results:Isolated rat hearts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recently, there has been increasing interest in the mechanistic relationship between cell death via apoptosis and oncosis [2,9] . Emerging evidence has suggested a complex interplay between these two cellular processes, which seem to have some common regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the mechanistic relationship between cell death via apoptosis and oncosis [2,9] . Emerging evidence has suggested a complex interplay between these two cellular processes, which seem to have some common regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, excitation–contraction uncouplers, such as 2,3‐butanedione monoxime, cytochalasin D and diacetyl monoxime, frequently used for optical mapping have been shown to have effects on action potential duration, conduction velocity, electrical restitution curve, calcium transient and ventricular fibrillation activation patterns (Qin et al 2003; Baker et al 2004; Cheng et al 2004; Kettlewell et al 2004). Additional evidence has shown that uncouplers affect metabolism, where the administration of 2,3‐butanedione monoxime before or after ischaemia increased myocardial ATP and reduced myocardial injury (Habazettl et al 1996; Moriguchi et al 2010). Hence, the methods used in this study offer the advantage of allowing the heart to contract freely and do not alter characteristics of energy metabolism or electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…11 studies (4,13,21,27,29,31,35,40,41,43) involved the effects of IPC on myocardium apoptosis index. The analysis showed that IPC reduced apoptosis level significantly (SMD -2.56, 95% CI -3.56 to -1.55, P<0.00001), and overall study heterogeneity was high (78%) ( Figure 5).…”
Section: Apoptosis Indexmentioning
confidence: 99%